90 - 70 - 90. - Sela, Rona (Tel Aviv : Tel Aviv Museum of Art, 1994)
Onne, Ella ; Ophir, Gilad ; Aya & Gal ; Asher, Yossi ; Ben-David, Arnon ; Breger, Yossi ; Barzilay, Tiranit ; Bracha, Ram ; Berest, Dganit ; Guetta, Judith ; Gechtman, Gideon ; Giotman, Yehoshua ; Garbuz, Yair ; Druks, Michael ; Weinfeld, Yocheved ; Zakhem, Dan ; Tal, Boaz ; etc.
90 - 70 - 90, Tel Aviv Museum of Art - Helena Rubinstein Pavilion for Contemporary Art, Tel Aviv, Opening; September 13th, 1994
boek